2021
DOI: 10.3889/oamjms.2021.4175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dawood Fasting on the Increased Level of Antioxidant Enzymes

Abstract: AIM: The aim of this study is to provide a comparative histopathological evaluation of the regeneration of bone defect filling with perforated antibiotic-impregnated bone allograft. MATERIALS AND METHODS: Seventy-two healthy rabbits (24 rabbits in each group) were used for this study. Bone defects (3-mm diameter, 10-mm depth) were created in the femur. Human femoral head prepared according to the Marburg bone bank system was used as a bone allograft. The control group did not receive any filling. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Additionally, this result is in line with a prior experiment conducted by Utami Mulyaningrum et al [61], which suggested that Dawood fasting (DF) might be used as a substitute for dietary restriction in order to raise SOD, GPx, and Cat antioxidant enzyme levels. This implies a DF increase in TAC levels.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, this result is in line with a prior experiment conducted by Utami Mulyaningrum et al [61], which suggested that Dawood fasting (DF) might be used as a substitute for dietary restriction in order to raise SOD, GPx, and Cat antioxidant enzyme levels. This implies a DF increase in TAC levels.…”
Section: Discussionsupporting
confidence: 89%
“…Based on observational studies in humans, Ramadan fasting has improved lipid profiles by reducing triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL) [10]. A study by Ma et al [5] in experimental animals reported that intermittent fasting had reduced glucose levels and enhanced hepatic metabolism, in line with other studies in which intermittent fasting reduces systemic oxidative stress and increases antioxidant enzymes in the liver as a central metabolic homeostasis organ [11], [12].…”
Section: Introductionmentioning
confidence: 76%
“…Such good bacteria also increase significantly in number after the diabetic mice, the villi were significantly longer than in the AL diet mice (22). Dawood fasting can inhibit cell death due to the increased formation of antioxidants, including superoxide dismutase, glutathione peroxidase and catalase (23). The antioxidants formed during fasting for fewer than 24 hours can prepare the body to cope with oxidative stress during the refeeding phase.…”
Section: Discussionmentioning
confidence: 99%